Yield and quality of fodder sorghum during summer season in southern Rajasthan as affected by the nitrogen levels and seed rates - Singh, Bahadur; Kaushik, M. K.; Jat, S. L.; Singh, Bhagwat (Annals of Agricultural Research, 2016)
A field experiment to evaluate the effect of nitrogen levels (40, 60, 80 and 100 kg N/ha) and seed rates(30, 35, 40 and 45 kg/ha) on fodder sorghum cv. SU-1080 was carried out at Udaipur. Nitrogen application significantly increased the green fodder and dry matter yield due to increased plant height and stem diameter. Crude protein content was also increased due to an increase in nitrogen level. However, increase in nitrogen level decreased the crude fibre, total digestible nutrient (TDN) and nitrogen free extract (NFE) percentage. Nitrogen application @ 100 kg/ha produced significantly highest green fodder yield (495.11 q/ha) which was statistically similar to 80 kg N/ha (462.0 q/ha). Increase in seed rate significantly increased the plant density, plant height, green and dry matter yield and its contents but decreased the stem diameter. Crude fibre, crude protein and ash contents were decreased with increased seed rate but could not reach to significant level. Seed rate of 40 and 45 kg/ha produced statistically similar green fodder yield (466.45 and 476.07 q/ha, respectively). Fodder sorghum sown with a seed rate of 40 kg/ha and supplied with 80 kg N/ha proved to be the best combination for getting higher green fodder yield and its quality during summer season in southern Rajasthan